Creditworthiness and climate: Identifying a hidden financial co-benefit of municipal climate adaptation and mitigation policies. (February 2019) - Rashidi, Kaveh; Stadelmann, Martin; Patt, Anthony
Abstract: Municipal policies can reduce greenhouse gas emissions and help to mitigate climate change. It is often unclear why cities would adopt such policies, however, given that the benefits from climate mitigation will be felt globally, rather than exclusively locally. Studies have identified a rationale for urban mitigation and energy policies rooted in local co-benefits, such as improvements in local environmental quality or job creation. Here we explore the possibility of financial co-benefits: whether municipal climate policies lead to an enhanced creditworthiness. This would translate into reduced borrowing costs for other infrastructure projects. Interviewing key informants from cities, investment firms and rating agencies, we find that rating agencies do consider climate policies in their ratings. This clearly applies to those climate policies that can result in demonstrable net economic gains to the municipality. However even those mitigation and energy policies that come at net costs to cities can have positive impacts on rating assessments, either because the policies are seen as reducing regulatory risks, or because they send positive signals to those investors having global sustainability agendas. Interestingly, those least aware of these factors appear to be city leaders themselves. This suggests a need to make them aware of how rating agencies and investors positively view climate mitigation policies.